2018
DOI: 10.1109/tip.2017.2767288
|View full text |Cite
|
Sign up to set email alerts
|

Saliency Detection Based on Multiscale Extrema of Local Perceptual Color Differences

Abstract: Visual saliency detection is a useful technique for predicting, which regions humans will tend to gaze upon in any given image. Over the last several decades, numerous algorithms for automatic saliency detection have been proposed and shown to work well on both synthetic and natural images. However, two key challenges remain largely unaddressed: 1) How to improve the relatively low predictive performance for images that contain large objects and 2) how to perform saliency detection on a wider variety of images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…A colour adaptation from Ishikura et al [9] extracts keypoints marginally in CIELAB colour space. Rassem and Khoo [10] measure quantified colour histogram to extract key-point.…”
Section: Corner Detectormentioning
confidence: 99%
“…A colour adaptation from Ishikura et al [9] extracts keypoints marginally in CIELAB colour space. Rassem and Khoo [10] measure quantified colour histogram to extract key-point.…”
Section: Corner Detectormentioning
confidence: 99%
“…The center-surround absolute difference on the biologically motivated fea-tures was first proposed by Itti et al 6 and is widely used to detect the local distinctive regions. 7,8 Later, by proposing a graph model to globally integrate the image regions, Harel et al showed that the global distinctiveness could better predict saliency. Further, the spatially weighted global absolute difference of image patches in the principal components space 9 or CIELab color space 3,10 also presents high accuracy in saliency detection.…”
Section: Introductionmentioning
confidence: 99%
“…This paper contributes toward saliency detection by exploiting IQA models. Many previous saliency models computed the absolute difference of features to measure the distinctiveness of image regions in the local 6,8 or global extent. 3,9,30 However, according to the studies on IQA, the structural similarity is validated as a better similarity measure than the absolute difference in the context of HVS perception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a region-based contrast was proposed to enhance the spatial information on the final saliency map. Ishikura et al [14] proposed an unsupervised saliency detection method based on multi-scale extrema of local perceptual color difference. However, their method was only used to estimate the locations, sizes, and saliency levels of candidate regions instead of the pixel-level saliency map.…”
Section: Introductionmentioning
confidence: 99%